Optimising the reach of mobile health messaging programmes: an analysis of system generated data for the Kilkari programme across 13 states in India. (8th August 2022) - Mohan, Diwakar; Bashingwa, Jean Juste Harrisson; Scott, Kerry; Arora, Salil; Rahul, Sai; Mulder, Nicola; Chamberlain, Sara; LeFevre, Amnesty Elizabeth
Abstract : Kilkari is an outbound service that makes weekly, stage-based, prerecorded calls about reproductive, maternal, neonatal and child health directly to families' mobile phones, starting from the second trimester of pregnancy and until the child is 1 year old. Since its initiation in 2012–2013, Kilkari has scaled to 13 states across India. In this analysis article, we explored the subscriber's journey from entry to programme to engagement with calls. Data sources included call data records and household survey data from the 2015 National Family Health Survey. In 2018, of the 13.6 million records received by MOTECH, the technology platform that powers Kilkari, 9.5 million ( 70%) were rejected and 4.1 million new subscribers were created. Overall, 21% of pregnant women across 13 states were covered by the programme in 2018, with West Bengal and Himachal Pradesh reaching a coverage of over 50%. Among new subscriptions in 2018, 63% were subscribed during pregnancy and 37% after childbirth. Of these, over 80% were ever reached by Kilkari calls and 39% retained in the programme. The main causes for deactivation of subscribers from the system were low listenership and calls going unanswered for six continuous weeks. Globally, Kilkari is the largest maternal mobile messaging programme of its kind in terms of number of subscribers but the coverage among pregnant women remains low. While call reach appears to be on the higher side, subscriber retention is low; this highlights broader challenges with providing mobile health services at scale across India.